2021
DOI: 10.3390/app11020703
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for the Knowledge Management Application in Maintenance Engineering: Perception from Maintenance Technicians

Abstract: Knowledge based on personal experience (tacit knowledge) acquired in problem solving actions and in maintenance actions is the fundamental basis for maintenance technicians in companies with great physical assets. Generally, there is no proper policy for managing strategic knowledge and its capture. In this article, through qualitative studies (grounded theory) and surveys conducted with technicians, the aim was to obtain the perception of the maintenance technicians’ part of the companies, in order to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…These collateral results are important in the operation and maintenance of this type of industrial plant [1,16], being one of the areas of concern to achieve efficient industries with respect to the environment [17][18][19][20]. With all this, the importance of combining different regulation systems in industrial refrigeration compressors is shown in order to improve energy efficiency, so that it can be understood by professionals in the sector and introduce new lines of research to improve the efficiency of these systems.…”
Section: Discussionmentioning
confidence: 99%
“…These collateral results are important in the operation and maintenance of this type of industrial plant [1,16], being one of the areas of concern to achieve efficient industries with respect to the environment [17][18][19][20]. With all this, the importance of combining different regulation systems in industrial refrigeration compressors is shown in order to improve energy efficiency, so that it can be understood by professionals in the sector and introduce new lines of research to improve the efficiency of these systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this area, issues such as knowledge management (e.g., [ 109 ]), machine learning (e.g., [ 22 , 88 ]), artificial intelligence (e.g., [ 110 , 111 , 112 ]), IoT technologies (e.g., [ 113 ]), or big data analyses (e.g., [ 114 ]) are addressed.…”
Section: Systematic Literature Review Of the Selected Papers Within T...mentioning
confidence: 99%
“…Another issue raised by Windelband (2017) is the level of expertise required of specialists while using user support technologies such as mobile apps, portals and so on. The industry currently lacks technicians skilled in digital technologies (Roda et al , 2018) and knowledge management (Cárcel-Carrasco and Cárcel-Carrasco, 2021). The above explanations indicate that present skill sets are insufficient to deal with I4.0 technologies, posing a severe challenge for maintenance contractors to attain.…”
Section: Identification Of Maintenance Outsourcing Challengesmentioning
confidence: 99%